As concepções alternativas de alunos da 8ª série do ensino fundamental sobre o fenômeno do efeito estufa - Libanore, Ana Cristina Leandro da Silva (2007)
To elucidate education and learning always went in general a challenge for all researchers and educators. Nowadays, the number of researches about sciences is growing, since, according to recent studies, the student formulates different conceptions from the scientific, during the teaching-learning process in the classroom. Such formulations built by students, interfering in a negative way for learning of the scientific knowledge. Besides, the teachers not seem to know as to approach the previous knowledge of students, when teaching at school scientific knowledge. Due to that reality, this work analyzes the students of the 8th series of Fundamental Teaching conceptions on the effect stove, theme that makes part of the curriculum and the subjects are: Sciences and Geography of this teaching level. The research involved 40 students and two teachers, that teaching Sciences and Geography of the Fundamental Teaching of private school of a municipal district of the Northwest area of the State Paraná. For collection of data, the students answered to a questionnaire and the teachers were interviewed. With base the analysis of data, it was verified that so much students as the teachers possess alternative ideas, regarding the effect stove, conceiving that phenomenon as a consequence of the human action, when polluting and to destroy the nature. It was also obvious that for them effect stove and global heating are synonymous, because the increase of skin cancer and the melting of the glaciers were explained as consequences of the effect stove. Others predominant conceptions were that the holes in the layer of ozone generate the effect stove and that our planet is compared exactly to a stove, because of the ultraviolet rays that penetrate for the holes of the layer of ozone and they increase the temperature in the Earth. Analyzing the didactic book adopted by the school, when those students did to 5th series in the subject is Geography, some of those alternative ideas were also verified. In that way, the analysis of the accomplished data indicates that the conceptual confusion manifested by the students and educators has it is roots in the teaching process and learning and it interferes sharply in the quality of the teaching of Sciences.